Predictors for DSM-5 nonsuicidal self-injury in female adolescent inpatients: The role of childhood maltreatment, alexithymia, and dissociation. (30th May 2016) - Lüdtke, Janine; In-Albon, Tina; Michel, Chantal; Schmid, Marc
Abstract: The purpose of this study was to examine the relationship between various adverse childhood experiences, alexithymia, and dissociation in predicting nonsuicidal self-injury (NSSI) in an inpatient sample of female adolescents. Seventy-two adolescents (aged 14–18 years) with NSSI disorder (n=46) or mental disorders without NSSI (n=26) completed diagnostic interviews and self-report measures to assess NSSI disorder according to the DSM-5 criteria, childhood maltreatment, alexithymia, and dissociation. Alexithymia and dissociation were highly prevalent in both study groups. Multivariate logistic regression analyses indicated that only alexithymia was a significant predictor for NSSI, whereas childhood maltreatment and dissociation had no predictive influence. The association between alexithymia and NSSI emphasizes the significance of emotion regulation training for female adolescents with NSSI. Efforts to reduce NSSI behavior should therefore foster skills to heighten the perception and recognition of one's own emotions. Highlights: We investigated female adolescents with NSSI disorder and clinical controls. We focused on the characteristics of alexithymia in NSSI disorder and examined the predictive power of childhood maltreatment, alexithymia, and dissociation. Alexithymia was a significant predictor for NSSI disorder, whereas childhood maltreatment and dissociation had no predictive influence. Our results emphasize the significance of emotion regulation training for female adolescents with NSSI.